A new species of Mimulopsis (Acanthaceae) from Rwanda and Burundi - Fischer, Eberhard (Phytotaxa, 2017)
A new species, Mimulopsis champluvierae, from Rwanda and Burundi is described. It differs from M. solmsii in the linear bracts with revolute margin, the long violet glandular hairs on the whole inflorescence including bracts and calyx, the two bracteoles that are at least half as long as the sepals, the linear sepals, the yellow corolla with purplish patterning, the capitate stigma, and the ovary with only a few hairs at the apex. The plietesial life history of M. champluvierae and M. arborescens is described. The typical M. solmsii and M. excellens show no pronounced mass-flowering, and single inflorescences are present almost every year.